A Life in Balkan Archaeology - Chapman, John, 1951- (Oxbow Books, Limited, 2021)
This lively memoir tells the story of a boy growing up in Plymouth, Devon, getting excited about archaeology after visits to mainland Greece and Crete, trying to get into Greek archaeology and relocating northwards into the Balkans, where he spent a career in prehistoric research. The chapters alternate between museum/university experiences and the author's major research projects. The experiences of working in that part of the world as the Third Balkan War was starting were dramatic. The memoir presents stories with implications for East-West relationships which will soon disappear from living memory. The ways that research projects originated and developed are also strongly featured. There is also a fund of anecdotes about prehistorians living and dead. The publication of this memoir records those fragments of the discipline's history which are in danger of being lost forever. But Chapman's life story is not erased from this account, which is not an anthropological work but, rather, a participant account with a modicum of relevant personal details. This memoir provides the insider story to the research results.